Do supportive family behaviors promote diabetes self-management in resource limited urban settings? A cross sectional study - Saranya Ravi; Swetha Kumar; Vijayaprasad Gopichandran (BMC, 2018)
Abstract Background Self-management is an essential component of prevention and treatment of type 2 diabetes. Social and family support has been shown to influence self-management behaviors as well as glycemic control and complications. This study was conducted to assess whether diabetes family support improves diabetes self-management and glycemic control in a typical urban population in India. Methods A cross-sectional study using a questionnaire that had items from the Summary of Diabetes Self Care Activities Scale (SDSCA), the Diabetes Family Behavior Checklist (DFBC) and some sociodemographic and diabetes related clinical data was conducted. The participants were consecutively sampled from the diabetes outpatient department in a tertiary care hospital in Chennai, south India. Results A total of 200 consecutive patients from the diabetes outpatient department were interviewed. Diabetes self-management practices were good with respect to avoiding fatty foods and carbohydrates and undergoing regular blood testing for glucose. But the self-management with respect to exercise and foot related care was rare. It was observed that a vast majority of the patients did not report receiving any support from their families. However, in the small proportion who did receive good family support, there is an association between diabetes self-management and diabetes family support (β = 0.527; p = 0.015). Further, the path model showed that there is a positive statistically significant association between family support score and the diabetes self-management score (β = 0.254, p < 0.001). However, the negative association between the diabetes self-management score and the mean plasma glucose did not reach statistical significance (β = − 46.378, p = 0.082). Conclusions In the urban south Indian setting, family support was significantly associated with better self-management activities, but better self-management did not reflect as better glycaemic control.